Wavelets in the prediction of short-time series - Hadaś-Dyduch, Monika (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2015)
The aim of this article is to present original application wavelets to the prediction of short-term of time series. The model proposed to predict short-term time series (in particular for predicting macroeconomic indicators) is a model of copyright. The model is based on wavelet analysis, the Haar wavelet, the Daubechies wavelet and adaptive models. The Daubechies wavelets are a family of orthogonal wavelets and are characterized by a maximal number of vanishing moments for some given support. Adaptive models have been appropriately modified by the introduction of a wavelet function and combined into one predictive model. The results obtained from the study results indicate that the authorial model is an effective tool for short-term predictions. The model was applied to predict macroeconomic indicators.
Mathematical Economics, 2015, Nr 11 (18), s. 43-54
Keywords: wavelets; prediction; Daubechies wavelets; Haar wavelet